Clinical Audit of Pediatric Advanced Life Support (PALS) Guideline Adherence during Emergency Resuscitation - Dr. Saima Saeed; Dr. Azka Haleem; Dr. Syeda Fiza; Dr. Sania Sehar; Dr. Nimra Aziz Qazi; Dr. Tooba Baig; Dr. Ahmad Yar, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Pediatric emergencies can progress rapidly to respiratory failure, shock, and cardiopulmonary arrest. Objective: To assess adherence to Pediatric Advanced Life Support guidelines during emergency resuscitation in the Pediatric Emergency Department and identify areas requiring quality improvement. Study Design: Clinical audit. Place and Duration of Study: Pediatric Emergency Department, Liaquat University Hospital, Hyderabad, from July 2021 to December 2021. Methodology: Ninety-six consecutive resuscitation events involving children aged one month to 18 years were assessed using a structured checklist based on Pediatric Advanced Life Support recommendations. The evaluated criteria included timely recognition of deterioration, initiation and quality of cardiopulmonary resuscitation, oxygenation and ventilation, rhythm recognition, vascular access, epinephrine administration, defibrillation, assessment of reversible causes, teamwork, documentation, and post-resuscitation care. Results: The mean overall adherence score was 61.4 ± 14.2%. High adherence was observed in 19 (19.8%) events, moderate adherence in 43 (44.8%), and low adherence in 34 (35.4%). Immediate cardiopulmonary resuscitation was initiated in 65 (67.7%) events. The recommended compression rate, appropriate compression depth, and interruptions below 10 seconds were achieved in 52 (54.2%), 47 (49.0%), and 43 (44.8%) events, respectively. Correct epinephrine dosing was documented in 60 (62.5%) events, while recommended dosing intervals were followed in 49 (51.0%). Conclusion: Adherence to Pediatric Advanced Life Support guidelines was suboptimal, particularly regarding chest-compression quality, medication timing, communication, documentation, and debriefing.